Systems modeling to improve river, riparian, and wetland habitat quality and area. (April 2020) - Alafifi, Ayman H.; Rosenberg, David E.
Abstract: Systems models to improve ecosystems often identify flows to meet minimum instream flow requirements or minimize deviations from a predefined flow regime. Here, we present a new systems optimization model that determines when, where, and how much to allocate scarce water, financial resources, and revegetation efforts to improve aquatic, floodplain, and wetland habitat areas and quality. This optimization is subject to constraints on water mass balance, vegetation growth, infrastructure capacities, and meeting existing agricultural and urban water demands. We followed a participatory approach to apply and validate our model in the Lower Bear River watershed, UT. Results show that increasing winter reservoir releases, minimizing spring spills, and planting native floodplain vegetation early in the growing season can increase suitable habitat area beyond managing water alone. Additional flow on the Little Bear River between August and December will most increase habitat area and quality compared to other locations. Highlights: A new ecological objective quantifies the suitable habitat areas of aquatic, floodplain, and wetland habitat types. A systems model shows when, where, and how much to allocate scarce resources to improve watershed habitat area and quality. Synergistic water and vegetation management can improve habitat for native fish, floodplain vegetation, and migratory birds. An open-access web map helps communicate opportunities to improve habitat area and quality to stakeholders.